Teacher knowledge: insights for continuing education in Southern Brazil - Fabiana Diniz Kurtz; Denilson Rodrigues da Silva; Maria Cristina Pansera de Araújo (Alteridad : Revista de Educación)
The pandemic caused by Covid-19 has caused education, on a global scale, to face increasing challenges in considerable aspects, from the social and economic inequality of students and teachers to the so-called learning deficit at all levels. Considering the essential dialogue between the university, through its teacher education courses and the basic education school, an applied research project was developed (participatory action research) whose theme presupposes technological innovation from a double perspective, as a means and an end. Means, through the proposed teaching methodology, integrated with technology with a view to changes and innovation in the work processes of basic education teachers when implemented. End, considering the pedagogical products generated after implementing the methodology, digital learning objects that, by nature, encompass different technologies for learning purposes. Furthermore, through the effective participation of teachers linked to the action research proposal, the results suggest the effectiveness of teaching resignification, made possible by continuing education, regarding their role as mediators and curators of the pedagogical process, aware that their knowledge of teacher involves the content, pedagogical and technological dimensions, as well as the role of information and communication technologies as an integral part of their pedagogical work.